2012
DOI: 10.1155/2012/357948
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and Genetics Aspects of Chagas Disease at Endemic Areas

Abstract: The etiologic agent of Chagas Disease is theTrypanosoma cruzi, transmitted through blood-sucking insect vectors of the Triatominae subfamily, representing one of the most serious public health concerns in Latin America. There are geographic variations in the prevalence of clinical forms and morbidity of Chagas disease, likely due to genetic variation of theT. cruziand the host genetic and environmental features. Increasing evidence has supported tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…These states present the highest prevalence of CD and CHD [31], which may be the result of the varying pathogenic degrees of T. cruzi [15]. Regional differences are associated with both disease severity and the predominance of clinical forms due to factors linked to the parasitized individual (immune status, nutritional status, genetic factors, and physical effort) and to other factors related to the parasite (different strains of T. cruzi, parasitism intensity, and reinfections) [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…These states present the highest prevalence of CD and CHD [31], which may be the result of the varying pathogenic degrees of T. cruzi [15]. Regional differences are associated with both disease severity and the predominance of clinical forms due to factors linked to the parasitized individual (immune status, nutritional status, genetic factors, and physical effort) and to other factors related to the parasite (different strains of T. cruzi, parasitism intensity, and reinfections) [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The balance between inflammatory and modulatory cytokines towards an anti-inflammatory profile contributes to the control of the disease and to the development of its milder forms. Conversely, severe diseased patients with the cardiac form developed a Th1-specific immune response with inflammatory infiltrate and tissue damage (172)(173)(174). Our group studied elderly adults from an endemic area for Chagas disease analyzing the correlation between serum levels of cytokines and chemokines, Trypanosoma cruzi infection, and cardiac abnormality (175).…”
Section: Chagas Diseasementioning
confidence: 99%
“…Recently, T. cruzi strains were reclassified into six DTUs (discrete typing units) called TcI to TcVI [22], and there is much speculation regarding whether this parasite variability could be associated with different disease prognoses. Although T. cruzi infection results in a broad spectrum of clinical forms as indeterminate, cardiac, and digestive forms, the determinant factors involved in the development of each clinical form have not been elucidated, though it is likely that genetic factors of the host and parasite are involved [23]. However, no study to date has found an unequivocal association between the infecting parasite DTU and the clinical forms of the disease.…”
Section: Introductionmentioning
confidence: 99%